Respuesta :

Answer:

Step-by-step explanation:

Pretty sure it’s C

For this case we must simplify the following expression:

[tex]\frac {\sqrt {c ^ 2 * d ^ 6}} {\sqrt {4c ^ 3 * d ^ {- 4}}}[/tex]

By definition of root properties we have to:

[tex]\sqrt [n] {a ^ n} = a ^ {\frac {n} {n}} = a[/tex]

Then, we can rewrite the expression as:

[tex]\frac {c ^ {\frac {2} {2}} * d ^ {\frac {6} {2}}} {2c \sqrt {c} * \frac {1} {d ^ {\frac {4} {2}}}} =[/tex]

[tex]\frac {c * d ^ 3} {2c \sqrt {c} * \frac {1} {d ^ 2}} =[/tex]

[tex]\frac {d ^ 3} {2 \sqrt {c} * \frac {1} {d ^ 2}} =[/tex]

We have to:

[tex]a ^ n * a ^ m = a ^ {n + m}[/tex]

Then, applying double c we have:

[tex]\frac {d ^ 5} {2 \sqrt {c}}[/tex]

Answer:

Option B